Evaluation of English Self-Learning Modules in the Implementation of Modular Distance Learning - Paul Joshua S. de Dios; Eunice Marie M. Bronzal; Airiks L. Lorda; Emharie D. Calleja; Cyra A. Carinan; Roldan C. Cabiles (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
In response to the call that education must continue in the midst of the COVID- 19 pandemic, Self-Learning Modules (SLM) became the Department of Education’s primary learning resource in the implementation of a wide-scale Modular Distance Learning. With the educational landscape being confronted with numerous concerns that questions the quality of its SLMs, their evaluation plays an extremely crucial role in pursuit of quality education. The study evaluated English Self-Learning Modules used by Grade 7 students in the First Quarter and propose an enhanced learning material that will be helpful in their modular distance learning experience. The study sought to answer the following questions: (1) What are the strengths and weaknesses of the Self-Learning Modules in terms of: Intellectual Property Rights Compliance, Learning Competencies, Instructional Design and Organization, Instructional Quality, Assessment, and, Readability?; (2) What are the Alternative Interventions suggested to strengthen the identified weaknesses in the Self-Learning Modules?; and, (3) What Enhanced Self-Learning Modules may be proposed based on the strengths and weaknesses of the evaluated materials? Using a purposive sampling, the Key Informants of the study included a total of eight (8) English teachers coming from three different secondary school locales from Legazpi City Division namely: Legazpi City National High School, Gogon High School and Cabangan High School. The study used a mixed method using a Descriptive –Evaluative Design where Key Informants answered a Survey Questionnaire and underwent Key Informants Interview to record the strengths and weaknesses of the Self-Learning Modules. Thematic analysis and percentage were used in the study to identify salient themes from qualitative and quantitative responses of the participants, respectively. Relevant findings revealed that the strengths of Self-Learning Modules are (1) accuracy in citations, (2) copyright compliance (3) proper acknowledgement of the references, (4) accuracy in content, (5) appropriate presentation of objectives, (6) logical organization of content, (7) integration of valuable traits, (8) development of 21st century skills, (9) alignment of assessments to lesson objectives and (10) appropriateness of content and vocabulary to the learners’ level. On the other hand, Self-Learning Modules displayed weaknesses on the following areas: (1) rotten links, (2) missing bibliographies and references, (3) unpacking of broad competencies (4) outdated content and information, (5) grammatical errors, (6) development of lessons that allow for review, (7) providing answer keys, (8) unclear presentation of instruction and (9) seamless transitions of lessons. To strengthen the identified weaknesses, the researchers developed a Guide Book that discusses the alternative interventions suggested by the researchers based on their insights together with the recommendations of educators. The Guide Book aims to empower every module user to become involved in creating an improved Modular Learning experience. Moreover, the Enhanced Self-Learning Modules offshoot retained the revealed strengths and carefully applied the alternative interventions to strengthen the weaknesses. Finally, specific recommendations were suggested aimed towards the improvement of learning experiences.